EFFECT OF SOME FLAVONOIDS ON THE ACTIVITY OF SUCCINATE DEHYDROGENASE IN LIVER MITOCHONDRIA (Universal International Scientific Journal, 2026)
This thesis studies the effect of some flavonoids on the activity of succinate dehydrogenase (SDH) enzyme in liver mitochondria. Succinate dehydrogenase is an important link in the cellular respiratory chain, and is the main enzyme connecting the tricarboxylate cycle and the electron transport chain. During the study, the modulatory properties of flavonoids obtained from natural sources on mitochondrial enzyme systems, their antioxidant activity, and their role in energy metabolism are analyzed. The results obtained indicate the potential importance of flavonoids in improving the bioenergetic state of liver cells or regulating enzyme activity under oxidative stress conditions. This scientific work has important theoretical and practical significance in the development of metabolic disorders and hepatoprotective agents
Keywords: flavonoids; liver mitochondria; succinate dehydrogenase